EFFECTS OF CHEMICAL CONTROL AGAINST PEAR PESTS (Scientific journal of the Fergana State University, 2026)
A lot of attention is paid to assessing the diversity of entomofauna of local areas rich in heavily developed and artificial ecosystems in the world, identifying their adaptation strategies and the characteristics of reproduction of harmful species. Pests are spreading widely in nature under favorable conditions. As a result of the extensive use of chemicals, fruit products become unfit for storage. It is impossible to use more than the norm of chemicals used in pear orchards. The interaction between insects and plants is not limited to the harm caused by insects to plants, but also depends on the impact of insects on the plant world.